Existence and iterative method for some fourth order nonlinear boundary value problems. (January 2019) - Wei, Yongfang; Song, Qilin; Bai, Zhanbing
Abstract: This work is devoted to proving the existence of the iterative solution to a fourth order boundary value problem. By the use of a novel efficient method for nonlinear fourth order boundary value problem, the existence and uniqueness of solution for the problem is obtained. The monotony of iterations is also considered. Some examples are presented to illustrate the main results.